Implementation of Stress Management to Decrease Blood Glucose Level of People with Diabetes Mellitus - Amira Bin Seh Abubakar; Rasdiyanah Muhlis; Fitriyanti Idrus (JURNAL INFO KESEHATAN, 2025)
Chronic hyperglycemia in patients with diabetes mellitus (DM) can be worsened by prolonged physical and emotional stress, which increases stress hormones like cortisol and raises blood glucose levels. Effective stress management is therefore essential to prevent glucose fluctuations and reduce the risk of diabetes-related complications. Techniques such as deep breathing exercises, progressive muscle relaxation, and hypnosis have been shown to lower stress hormones, enhance endorphin release, and improve glycemic control. This study aimed to measure patients' blood sugar levels before and after administering stress management interventions, including deep breathing relaxation techniques and five-finger hypnosis. The study method used a quasi-experimental design with a pre- and post-test approach, without a control group, was used. A total of 61 DM patients from the Diabetes Center in Ternate City were recruited through simple random sampling. The intervention consisted of deep breathing exercises, progressive muscle relaxation, and five-finger hypnosis. Blood glucose levels were measured before and after the intervention. Data analysis involved paired t-tests, ANOVA, and correlation tests. The results showed that the mean blood glucose level decreased from 215.75 mg/dL to 209.62 mg/dL following the intervention, with a mean difference of -6.13 mg/dL. However, this reduction was not statistically significant (p = 0.0593; α = 0.05). It was concluded that there was a decrease in blood glucose levels after the intervention, although the difference was not statistically significant.  The application of this study suggests that stress management techniques such as deep breathing, relaxation, and five-finger hypnosis may provide benefits in managing stress. Further studies using controlled designs and larger sample sizes are recommended.